Using borehole radar detecting hydraulic fracturing crack in near horizontal holes in coal mine - Bici, Jiang (Frontiers in Earth Science, 2024)
Currently, hydraulic fracturing technology is widely implemented for controlling the surrounding rock and enhancing permeability in low-permeability coal seams. Evaluating the effectiveness of hydraulic fracturing is a critical component of hydraulic fracturing operations. This study addresses the challenges in assessing the location, extension angle, and initial width of fracturing fractures within the current framework of hydraulic fracturing effectiveness evaluation in coal mines. We propose utilizing single-hole reflection borehole radar to evaluate the hydraulic fracturing effect, and through numerical simulation, we analyze the response characteristics of borehole radar when detecting various hydraulic fracturing-induced cracks.Initially, five models representing hydraulic fracturing cracks and two models for non-hydraulic fracturing cracks were established. Subsequently, the responses of borehole radar with central frequencies of 100MHz, 200MHz, and 400MHz to cracks of identical shapes were analyzed. Additionally, the response characteristics of borehole radar with a 200MHz central frequency to cracks of varying lengths (1m, 2m, 3m), widths (4cm, 8cm, 40cm), and angles (90 °, 45 °, 15 °) were examined. Finally, a comparative analysis was conducted between hydraulic and non-hydraulic fracturing cracks. A branch hole was employed to simulate a hydraulic fracturing crack, allowing for an analysis of the borehole radar's response characteristics in practical scenarios. The findings indicate that borehole radar is a viable tool for assessing hydraulic fracturing effects, providing a theoretical foundation for identifying the position of cracks, evaluating their effectiveness, and determining the regional effectiveness of the hydraulic fracturing crack system.